Actin Polymerization Defects Induce Mitochondrial Dysfunction in Cellular Models of Nemaline Myopathies - Rocío Piñero-Pérez; Alejandra López-Cabrera; Mónica Álvarez-Córdoba; Paula Cilleros-Holgado; Marta Talaverón-Rey; Alejandra Suárez-Carrillo; Manuel Munuera-Cabeza; David Gómez-Fernández; Diana Reche-López; Ana Romero-González; José Manuel Romero-Domínguez; Rocío M. de Pablos; et al. (MDPI AG, 2023)
Nemaline myopathy (NM) is one of the most common forms of congenital myopathy and it is identified by the presence of "nemaline bodies" (rods) in muscle fibers by histopathological examination. The most common forms of NM are caused by mutations in the Actin Alpha 1 (ACTA1) and Nebulin (NEB) genes. Clinical features include hypotonia and muscle weakness. Unfortunately, there is no curative treatment and the pathogenetic mechanisms remain unclear. In this manuscript, we examined the pathophysiological alterations in NM using dermal fibroblasts derived from patients with mutations in ACTA1 and NEB genes. Patients' fibroblasts were stained with rhodamine-phalloidin to analyze the polymerization of actin filaments by fluorescence microscopy. We found that patients' fibroblasts showed incorrect actin filament polymerization compared to control fibroblasts. Actin filament polymerization defects were associated with mitochondrial dysfunction. Furthermore, we identified two mitochondrial-boosting compounds, linoleic acid (LA) and L-carnitine (LCAR), that improved the formation of actin filaments in mutant fibroblasts and corrected mitochondrial bioenergetics. Our results indicate that cellular models can be useful to study the pathophysiological mechanisms involved in NM and to find new potential therapies. Furthermore, targeting mitochondrial dysfunction with LA and LCAR can revert the pathological alterations in NM cellular models.